Applying International Humanitarian Law in Judicial and Quasi-Judicial Bodies International and Domestic Aspects - Jinks, Derek; Maogoto, Jackson N.; Solomon, Solon; SpringerLink (Online service) (The Hague : T.M.C. Asser Press : Imprint: T.M.C. Asser Press, 2014)
International humanitarian law has been perceived till now as encompassing only judicial cases concerning refugee protection or war crimes prosecutions, particularly in domestic fora. Yet, the last decade has witnessed a revolution in the way judicial bodies$1 (Binternational and domestic alike$1 (Bare ready to tackle complex security aspects pertaining to the laws of war. The present volume follows the international and domestic courts$1 (Bjurisprudential evolution as they deal with issues like the classification of armed conflicts, direct participation in hostilities and the nexus between international humanitarian law and human rights law. Projecting the field$1 (Bs jurisprudential development, the volume examines the role of international humanitarian law also in the realms of quasi-judicial bodies. Derek Jinks, University of Texas, School of Law, Austin, Texas, USA. Jackson Nyamuya Maogoto University of Manchester, School of Law, Manchester, UK. Solon Solomon King$1 (Bs College London, Dickson Poon School of Law, London, UK.s
Introducing International Humanitarian Law to Judicial and Quasi Judicial Bodies -- Applicability Test of Additional Protocol II and Common Article 3 for Crimes in Internal Armes Conflict -- The Role of the U.S. Judicial Branch During the Long War: Drone Courts, Damage Suits, and Freedom of Information Act (FOIA) Requests -- International Humanitarian Law in the Maritime Context: Conflict Characterization in Judicial and Quasi-Judicial Contexts -- Domestic Humanitarian Law: Developing the Law of War in Domestic Courts -- The Interaction of the International Terrorism Suppression Regime and IHL in Domestic Criminal Prosecutions: The UK Experience -- Beyond Life and Limb: Exploring Incidental Mental Harm under International Humanitarian Law -- Armed Conflict and the Inter-American Human Rights System: Application or Interpretation of International Humanitarian Law? The European Court of Human Right$1 (Bs Engagement with International Humanitarian Law -- The Interaction between Domestic Law and International Humanitarian Law at the Extraordinary Chambers in the Courts of Cambodia -- Applying the Laws of Armed Conflict in Swiss Courts -- International Humanitarian Law in the Courts of Australia -- Aut Deportare Aut Judicare: Current Topics in International Humanitarian Law in Canada -- International Humanitarian Law in Indian Courts: Application, Misapplication and Non-Application -- Interpretations of IHL in Tribunals of the United States -- The International Commission of Inquiry on Darfur and the Application of International Humanitarian Norms -- The Mavi Marmara Incident and the Application of International Humanitarian Law by Quasi-Judicial Bodies.s
Keywords: Law; Public international law; International humanitarian law; Law; International Humanitarian Law, Law of Armed Conflict; Public International Law; Electronic books